Rap and singing are used by music therapists to enhance emotional self-regulation of youth: Results of a survey of music therapists in the Netherlands. (April 2017) - Uhlig, Sylka; Dimitriadis, Theo; Hakvoort, Laurien; Scherder, Erik
Highlights: High agreement among music therapists on treatment goals for at-risk youth. Rapping and singing applications enhance self-regulative skills. Rapping aims to structure emotional expression and helps to regulate aggression. Singing supports expression of deeper emotional involvement. Rap & Sing Music-Therapy protocols are needed for higher quality of treatment. Abstract: The purpose of this study was to examine approaches of music therapists towards the application, frequency, and function of rap and sing engagements. Identification of these characteristics might support the refinement of these therapeutic interventions and encourage detailed application. A 25-question survey was sent to 336 qualified music therapists in the Netherlands. The questions sought information on such aspects as the role of rhythm in rapping and of melody in singing, the frequency of these applications in music therapy practice, and the treatment goals with reference to the needs of the clients. Results indicated that both rapping and singing applications in music therapy can enhance self-regulative skills during the process of emotional expression. In particular rapping occurred in this study considerably less frequent than singing but considered to decrease aggressive behavior. Singing was applied daily and associated with the support of deeper emotional involvement. The results suggest the need for more consistent descriptions of therapeutic interventions for the use of rap styles in music therapy practice, and the development of specialized protocols for research studying its effects for quality improvement.